Tinjauan Batasan Perlindungan dan Peringanan Hukum Bagi Justice Collaborator dalam Perspektif Tindak Pidana Pembunuhan Berencana - Amira Nabila Putri (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Premeditated murder is murder carried out using deliberate thought and planning. To help reveal the truth in cases that are difficult to uncover in the crime of premeditated murder, a Justice Collaborator is needed. The research methodology to be used is a normative juridical legal research approach. This writing requires a careful review of various theories and concepts, as well as a comprehensive review of the laws and regulations relevant to the subject matter under study. Justice Collaborator is an individual who is involved as one of the perpetrators in a certain criminal offense, has admitted his involvement in the crime, but is not the main perpetrator and provides testimony in legal procedures in court. Justice Collaborators have an important role so that they are entitled to protection and appreciation for their assistance. In SEMA No. 4/2011, the crime of premeditated murder is not clearly regulated and also not classified as